Error cascade in taxonomy: The case of Cardiomya perrostrata (Mollusca: Bivalvia: Cuspidariidae) in Brazilian waters - Oliveira, Cléo D. C.; Sartori, André F.; Absalão, Ricardo S. (Zootaxa, 2017)
Successions of erroneous taxonomic identifications in biodiversity studies are an undesirable but not rare phenomenon. Such cascades of errors frequently involve taxa with few, polymorphic diagnostic characters, such as representatives of the cuspidariid genus Cardiomya. Four species of the genus are believed to live in Brazilian waters: C. cleryana (d’Orbigny, 1842), C. ornatissima (d’Orbigny, 1853), C. striata (Jeffreys, 1876) and C. perrostrata (Dall, 1881). Many reported occurrences of these species are based on misidentifications, but the error cascade of incorrect records of C. perrostrata is by far the most extensive. Although the species has been reported to live in Brazilian waters for about half a century, all previous records seem to be based on a succession of mistaken identifications. This paper redescribes C. perrostrata based on an analysis of the type series, several lots of museum vouchers and new material collected in the Campos Basis (Rio de Janeiro, Brazil). Ontogenetic changes in shell outline and ultrastructural details of the hinge plate, periostracal surface and larval shell are described and illustrated for the first time. Based on a critical appraisal of the literature, we present an updated geographic and bathymetric distribution of the species. Cardiomya perrostrata displays a gradual increase in the relative length of the rostrum during its ontogeny and in larger specimens the rostrum is more prominently curved upwards. The larval shell is of type 2D, measuring about 215–235 μm in length. The periostracum is minutely pitted and a lithodesma is present. Its distribution is Western Atlantic, ranging from 42°N to 30°S, in depths of 18 to 1646–1829 m. Cardiomya knudseni (Allen & Morgan, 1981), a possibly related amphi-Atlantic species whose type material has been lost, is regarded herein as a nomen dubium.